Beyond Poet Voice: Sampling the (Non-) Performance Styles of 100 American Poets - Marit J. MacArthur; Georgia Zellou; Lee M. Miller (Journal of Cultural Analytics, 2018)
Literary readings provoke strong feelings, which feed intense critical de-bates. And while recorded literary readings have long been available for study, few scholars have applied to them the empirical methods that the digitalhumanities and interdisciplinary sound studies now offer.